Legal development on management of strata dispute in peninsular Malaysia - Mohamad, Nor Asiah; Sufian, Azlinor (Academy of IRMBR, 2013)
Strata living brings people of diverse interests, different cultures, values, ages and backgrounds under one roof. With that background, it is usual to have differences and disputes. While many would generally believe that problems can be resolved by prople involved talking about their problems and fulfilling their expected responsibilities, more often than not, more formal measures are needed. This paper highlights some approaches to improve the way strata disputes are resolved with reference to the newly approved Bill of Strata Management 2013. Under the Strata Titles Act 1985 and Building and Common Property (Management and Maintenance) Act 2007, when the issues cannot be resolved informally, the laws offer a number of mechanisms to resolve disputes, including reference to the High Court for serious matter.However, there are demands and suggestions for alternatives to the current options and the government has taken initiative to review the laws to include among others, tribunal for strata to resolve disputes in strata properties. This paper traces problems on strata properties management from case law, identifies the limitations in the current system, and highlights the proposed improvement in the new Bill. The result shows that Malaysia still lacks consultation to gather input from strata owners, tenants, strata council members, strata associations, other stakeholders and the general public. Though there are new initiatives introduced in the new law, it is doubtful whether the improvements suit the needs of those involved in strata properties.